The Effect of Dyeing Temperature on The Color and Color Fastness of Sicerek Leaves (Clausena Excavata Burm. F) on Roberto Cavali Fabric - Siti Aisyah Nabila; Samuel Martin Pradana; Adriani; Sri Zulfia Novrita; Hadiastuti; Vina Oktaviani (SAINTEKS : Jurnal Sain dan Teknik, 2026)
The industry produces synthetic dye waste that has the potential to damage the environment, so that more environmentally friendly natural dye alternatives are needed. One of the plants that has the potential to be used as a source of natural dyes is the sicerek leaf (Clausena excavata Burm. F), because sicerek leaves contain flavonoid compounds that can produce color. This study aims to analyze the color names and color fastness to washing on Roberto Cavali's fabrics whose writings use sicerek leaf extract at various dyeing temperatures. The method used is the experimental method. Identification of color names was carried out by involving 18 panelists as respondents and supported by the use of the Colorblind Assistant application to assist in color determination. Meanwhile, color fastness to washing was tested using a gray scale and a staining scale according to SNI ISO standards. Data analysis used is descriptive statistical analysis and simple linear regression tests. The results of the study show (1) Differences in dyeing temperatures produce different color names, RGB values ??and hexadecimal codes at various dyeing temperatures. (2) The dyeing temperature does not have a significant effect on color fastness based on gray scale testing as proven by a simple linear regression test with a Sig. value. 0.351 > 0.05 which indicates that there is no difference or is not significant. Meanwhile, testing using a coloring scale at temperatures of 30?C, 60?C and 90?C shows a value of 4-5 with a good category for various types of multifiber including wool, acrylic, polyester, nylon, cotton and acetate. (3) The dyeing temperature of 90?C is the most optimal temperature in producing color and color fastness.